PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS REACT PADA POKOK BAHASAN HIDROKARBON KELAS XI SMA - Della Permatasari; Elva Yasmi; Susilawati Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to develop and produce Student Worksheet Based REACT on the subject of Hydrocarbon in Class XI SMA which are valid and got positive response from Student Worksheet users. This development research used a 4-D model that has 4 stages, namely, Define, Design, Develop and Disseminate, but the research only reached the Develop stage. To produce a valid Student Worksheet, the Student Worksheet validity test is carried out which includes five aspects of assessment, namely aspects of content feasibility, aspects of REACT characteristics, linguistic aspects, aspects of presentation and graphic aspects. To know the response of Student Worksheet users, limited trial were conducted at SMAN 4 Pekanbaru and SMAN 6 Pekanbaru. The results of the study that have been validated by 3 validators state that the percentage is 92.33%. The results of the test questionnaire response to the Student Worksheet based on REACT with 30 students were 93% and the results of the responses from 2 chemistry teachers were 92.86%. Based on the principle of validation and limited testing, Student Worksheet Based on REACT in Hydrocarbon of Chemistry in Senior High School at Class XI the was declared valid and get positive responses from Student Worksheet user.Key Words: Student Worksheet, REACT, Hydrocarbon, 4-D Model